Timor Deer (Cervus Timorensis) Arrest System Marind People with Tidal Local Wisdom - Dirwan Muchlis; N. Nurcholis (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2019)
Deer are wildlife that has economic value because it can produce meat, leather, and velvet (young horn). Deer populations in nature have decreased due to uncontrolled wild poaching and damage to habitat. Indonesia has five types of deer, i.e., Cervus unicolor, Cervus timorensis, Axis kuhlii, Muntiacus Muntjak, and Axis axis (deer total). However, deer in Indonesia that have the opportunity to be empowered, there are several types, namely Cervus timorensis, Cervus unicolor and Axis axis, and in Merauke, especially in the had tribe0 has its distinctive characteristic in the process of catching deer. The purpose of the study was to know the pattern of deer arrest by the Malind tribe. The method used in this research is to conduct surveys and Wawan ways as well as observation of the field, the data in the analysis in a descriptive approach to conclude the investigation. The results showed that the pattern of deer caught in the Marind tribe traditionally done with snares, bamboo rinsing, as well as patterns carried out covering the forest burning Sawvana in the dry season of the cattle, besieged fire and dwelling on the land, and the season The community rained to the deck area (dense forest) that became the deer's dwelling and avoided the puddle of the sea, and the community captured it quickly. The chance of this research is the process of catching deer, in general, is done by the had in 2 ways that in the summer by burning and drought with the trap system.